Efeito do mutualismo entre formigas e insetos fitófagos na estrutura e estabilidade da comunidade de artrópodes associados a Psittacanthus robustus (Loranthaceae) - Freitas, Julia Dias de [UNIFESP] (2013)
The study of mutualistic interactions between ants and phytophagous insects is relevant, since it affects the structure and stability of ecological communities. Here, the mutualistic interaction between phytophagous insects and ants inhabiting the host plant known as mistletoe (Psittacanthus robustus (Loranthaceae) was studied in the Serra do Cipó, an outcrop located in Minas Gerais, southeastern Brazil. It was tested the hypothesis that this mutualistic interaction affects the structure and stability of arthropod communities associated with P. robustus, increasing the abundance and species richness in the absence of mutualism, with concomitant decrease in community stability. Exclusion experiments (i.e., ants and trophobionts) were carried out, forming three experimental groups: with mutualism (control), with ant exclusion only, and without ants and trophobionts (total exclusion). Periodical surveys of the arthropod community were established, and organisms were separated according to their functional groups. Significant changes were not observed among treatments with respect to local diversity (alpha diversity), considering communities as a whole. The same pattern was observed for most functional groups, with exception to the predators. However, it was confirmed the formation of a mosaic, characterized by plants with and without ant-trophobiont mutualism, enhancing beta diversity (diversity among habitats). Considering turnover percentages, greater stability was found in the experimental group with ant exclusion only. This study was also important to characterize the arthropod community associated with P. robustus.